Report on conference of indigenous peoples (Unique Printers KingstownVC, 1987)
Objectives of conference were to give recognition to indigenous people of the region; to critically analyse their social, economic and political context and to identify main issues of concern; to share views on how to address their needs and to establish a basis for greater integration between indigenous peoples. Activities included field trips to indigenous areas; presentations and discussions on sub-themes including isolation and underdevelopment,struggle for survival and recognition. Recommendations touch areas including education, culture, religion, economic development, media, and structures. Outlines 5 point conference declaration.
Theme: Caribbean indigenous revival : towards greater recognition and development